2023
DOI: 10.1088/1742-6596/2501/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Gear Profile Measurement Based on Thin Line Structured Light

Abstract: In order to achieve the high precision 3D measurement of gear tooth profile, a telecentric optical measurement system with large FOV (field of view), WD (working distance) and measuring range was proposed, the system was applied to the gear tooth profile measurement experiment and obtained a good effect. Firstly, the composition and the principle of the system were introduced. The lights of projection and imaging with an angle of 45° from the normal line of the measured surface can reduce the requirement of DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…At present, no research has been found on simultaneous online visual measurement of inner diameter, outer diameter, and thickness of disk parts. Furthermore, some studies [ 11 13 ] use telecentric lenses to improve measurement accuracy, but telecentric lenses with high cost, small field of view, low measurement efficiency, and low universality, which make it difficult to satisfy the requirements of in-situ applications.…”
Section: Introductionmentioning
confidence: 99%
“…At present, no research has been found on simultaneous online visual measurement of inner diameter, outer diameter, and thickness of disk parts. Furthermore, some studies [ 11 13 ] use telecentric lenses to improve measurement accuracy, but telecentric lenses with high cost, small field of view, low measurement efficiency, and low universality, which make it difficult to satisfy the requirements of in-situ applications.…”
Section: Introductionmentioning
confidence: 99%